On-line student feedback: a pilot study - Liz Barnett; Jane Galbraith; Paul Gee; Fran Jennings; Ron Riley (Association for Learning Technology, 2001)
Student feedback on courses has been a standard feature of university life for several years, with a substantial research backing to it (see, for example, reviews by Marsh, 1987; Marsh and Dunkin, 1992). Most feedback systems endeavour to serve more than one purpose, with student feedback forming part of the evidence used by: • individual teachers to improve teaching • heads of departments to monitor and guide individual teachers, especially part-time teachers; • course leaders for course development; • senior managers to make decisions on probation and promotion related to teaching performance; consider changes to the wider learning environment; help with the marketing of programmes; • external agencies to assess quality of provision